The Index Offence Representation Scales; a predictive clinical tool in the management of dangerous, violent patients with personality disorder?. (4th October 2013) - McGauley, Gill; Ferris, Scott; Marin‐Avellan, Luisa; Fonagy, Peter; McMurran, Mary; Taylor, Pamela
Abstract Background Forensic mental health professionals attach considerable importance to their patient's description of his or her index offence. Despite this, there is no systematic approach to examining and formulating the patient's offence narrative. Aim To use the index offence narratives and capacity to mentalize of violent offender‐patients with personality disorder to develop a tool to predict their progress and to evaluate that tool. Method In a prospective, cohort study, the index offence narratives of 66 violent high security hospital patients with personality disorder were obtained from a semi‐structured interview and used to generate the Index Offence Representational Scales (IORS). The predictive validity of these scales was investigated across a range of outcome variables, controlling for the association between initial and final value of the dependent variable. Results The degree to which patients held internal representations of interpersonal violence and malevolence, as measured by the IORS, predicted subsequent violent behaviour. In contrast to their actual aggressive behaviour, these patients rated themselves as having fewer symptoms on the Symptom Checklist‐90‐R (SCL‐90‐R) and fewer problems in interpersonal relationships on the Inventory of Interpersonal Problems. A more empathic victim representation on the IORS predicted better engagement with treatment. Conclusions The IORS show promise for helping clinicians formulate the early institutional pathway of seriously violent people with personality disorder, particularly with respect to their overt aggression and prosocial engagement. Replication studies are, however, indicated. Copyright © 2013 John Wiley & Sons, Ltd.